PERANCANGAN LIE DETECTOR MENGGUNAKAN ARDUINO - Imam Yunianto (Jupiter: Journal of Computer & Information Technology, 2022)
In this paper, the author will discuss various method approaches that have been developed to detect lies, including the detection of lies based on skin conductivity, handwriting form, written content, voice analysis, thermography, and gestures. Lie Detector is very helpful in the process of revealing a crime case with the method of investigating the perpetrator of a crime. Disclosing a statement or confession from a criminal with a Lie Detector seeing and analyzing the polygraph on the Lie Detector. However, Li's design of This e Detector with Arduino is not encouraging with unintended results. The author has tried to imp